Primary Osteosarcoma of the Breast in a Patient Treated Previously for Invasive Ductal Carcinoma: An Unusual Presentation of a Very Rare Primary Breast Malignancy - David Malcolm Milne; Navin Sookar; Srikanth Umakanthan; Fidel Rampersad; Lyronne Olivier; Jameel Ali (Case Reports in Surgery)
Primary osteogenic sarcoma of the breast is a rare clinical entity with few cases described in the literature. Unfortunately, the prognosis for these patients is poor when compared to invasive carcinomas of the breast. We report a case of a 58-year-old female who developed a primary osteogenic sarcoma of the breast five years after being treated for invasive carcinoma of the ipsilateral breast without the use of radiotherapy.